Correlates of poor clinical outcomes related to COVID-19 among older people with psychiatric illness - a mixed methods study - Abdulrahman, Surajudeen; Al-Balushi, Naser; Holdcroft-Long, Jason; Khan, Uzma; Ravindran, Bipin; Das, Sujata; Rajkumar, Anto P (International journal of psychiatry in medicine, 2023)
Objective COVID-19 may lead to a range of clinical outcomes among older people with psychiatric and medical conditions. Evidence guiding management of future outbreaks among this vulnerable population in psychiatric hospital settings are sparse. In this study, we examined the correlates of poor clinical outcomes related to COVID-19 and explored the perspectives of COVID-19 survivors hospitalized in psychiatry settings. Method The correlates of poor clinical outcomes related to COVID-19 were examined using a retrospective chart review of 81 older people hospitalized in psychiatry settings. Correlates of clinical outcomes related to COVID-19 were assessed by multiple logistic regression models. In addition, the perspectives of 10 COVID-19 survivors were explored by qualitative interviews. The qualitative data was subject to thematic analysis. Results Although 25.9% (n = 21) participants were asymptomatic, there was high COVID-19 related mortality (14.8%; n = 12). Vitamin-D deficiency, anticholinergic burden, and isolation policies within psychiatric wards were significantly (p < 0.05) related to COVID-19 related deaths. In qualitative interviews, participants emphasized the importance of strengthening local support networks and making vaccination centers more accessible. Conclusions Reducing anticholinergic prescriptions and improving isolation policies may help to mitigate poor clinical outcomes. Future research investigating the impact of vitamin-D supplementation on COVID-19 related outcomes is warranted.